2020
DOI: 10.1016/j.ekir.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Nephrology Literature for Transparency and Reproducibility Indicators: Cross-Sectional Review

Abstract: Introduction: Reproducibility is critical to diagnostic accuracy and treatment implementation. Concurrent with clinical reproducibility, research reproducibility establishes whether the use of identical study materials and methodologies in replication efforts permits researchers to arrive at similar results and conclusions. In this study, we address this gap by evaluating nephrology literature for common indicators of transparent and reproducible research. Methods: We searched the National Library of Medicine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
2
11
1
Order By: Relevance
“…The observation of the low availability of data and code in cancer research, as well as medical research more broadly, is not new. Rather our observations that 19% and 4% of cancer researchers declared data and code were publicly available are consistent with several previous studies reporting low, but increasing, declaration rates ranging between 3-24% and 0-2% respectively across a number of other medical fields between 2014 and 2018 [14][15][16][17][18][19][20][21][22][23][24], as well as more recent estimates [25][26][27].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The observation of the low availability of data and code in cancer research, as well as medical research more broadly, is not new. Rather our observations that 19% and 4% of cancer researchers declared data and code were publicly available are consistent with several previous studies reporting low, but increasing, declaration rates ranging between 3-24% and 0-2% respectively across a number of other medical fields between 2014 and 2018 [14][15][16][17][18][19][20][21][22][23][24], as well as more recent estimates [25][26][27].…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, we noted that only one of the 59 articles that declared data was available complied with our FAIR assessment. This observation, depending on how availability for reuse is defined, is unfortunately consistent with this body of research which has reported 50-100% reductions in availability following interrogation of sharing statements [14][15][16][17][18][19][20][21][22][23][24]; with factors such as the lack of unique and permanent identifiers, meta-data and licensing terms being noted as major pitfalls [32,52]. Furthermore, while we also noted a strong relationship between mandatory data sharing policies and actual data availability, we unfortunately also observed similarly sub-optimal compliance with these policies too; a finding that has been noted by other studies both inside and outside of medicine [28,53,54].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations